PENERAPAN PEMBELAJARAN INKUIRI DALAM MENINGKATKAN KEMAMPUAN BERPIKIR KRITIS MATEMATIS SISWA SMK - Safitri, Ajeng Dwiyani; Mustika Sari, Rika Mulyati (JP2M (Jurnal Pendidikan dan Pembelajaran Matematika), 2024)
The research aims to be able to find out the applications of inquiry learning using exponential material which can improve the mathematical critical thinking skills of vocational school level students in Bekasi Regency. This research approach uses descriptive methods of analysis in testing and observing the improvement of the ability to think critically mathematically of learners, test instruments are used in the form of questions on students' mathematical critical thinking skills on exponent material. The results showed a percentage score of 100% for six students classified as "very critical"; 80% percentage for six students who fall into the critical category; 60% percentage for six students who fall into the less critical category; and a 40% rate for four students who fall into the non-critical category. It can be concluded that the inquiry-based learning model used to improve students' critical thinking is successful.